Ecological system theory and community participation to promote healthy food environments for obesity and non-communicable diseases prevention among school-age children - Suwannawong, Pennapa Ritwong; Auemaneekul, Naruemon; Powwattana, Arpaporn; Chongsuwat, Rewadee (Public health nutrition, 2023)
To implement and evaluate the effectiveness of the community participatory program between school and family based on ecological system theory and participatory action research. The intervention covers three levels at the individual, family and school levels and involves educating students and parents by using technology, reducing sedentary behaviours, increasing exercise and changing to healthy food environments at school and at home. A quasi-experimental design was used in this study. Public primary school in Thailand. The participants in the study included 138 school-age children in grades 2-6 with their parents/guardians. The control group consisted of 134 school-age children at a school of the same size with their parents guardians. Results show that nutritional status was significantly improved within the experimental group ( value = 0·000) and between groups during follow-up ( value = 0·032). Students' knowledge about obesity and non-communicable chronic diseases (NCD) prevention, as well as physical activity and exercise behaviours, in the experimental group was significantly higher than that in the control group ( value = 0·000 and 0·044, respectively). Parents' perceptions of child obesity and family modelling behaviours in the experimental group were also significantly higher than that in the control group; value = 0·013 and 0·000, respectively). The community participation program was found to be successful. Not only students, families and schools improved health behaviours and healthy food environments at home and school, but the students' long-term nutritional status also improved.